Bacterial co-infection at hospital admission in patients with COVID-19. (May 2022) - Moreno-García, Estela; Puerta-Alcalde, Pedro; Letona, Laura; Meira, Fernanda; Dueñas, Gerard; Chumbita, Mariana; Garcia-Pouton, Nicole; Monzó, Patricia; Lopera, Carlos; Serra, Laia; Cardozo, Celia; Hernandez-Meneses, Marta; et al.
Highlights: Over 9% of patients hospitalized for COVID-19 will present a co-infection. Independent risk factors for co-infection were identified. When procalcitonin values are <0.2 ng/mL, co-infection is very rare. High ferritin values and oxygen saturation >94% are also uncommon in co-infection. ABSTRACT: Objectives: We described the current incidence and risk factors of bacterial co-infection in hospitalized patients with COVID-19. Methods: Observational cohort study was performed at the Hospital Clinic of Barcelona (February 2020–February 2021). All patients with COVID-19 who were admitted for >48 hours with microbiological sample collection and procalcitonin (PCT) determination within the first 48 hours were included. Results: A total of 1125 consecutive adults met inclusion criteria. Co-infections were microbiologically documented in 102 (9.1%) patients. Most frequent microorganisms were Streptococcus pneumoniae (79%), Staphylococcus aureus (6.8%), and Haemophilus influenzae (6.8%). Test positivity was 1% (8/803) for blood cultures, 10.1% (79/780) for pneumococcal urinary antigen test, and 11.4% (15/132) for sputum culture. Patients with PCT higher than 0.2, 0.5, 1, and 2 ng/mL had significantly more co-infections than those with lower levels (p=0.017, p=0.031, p<0.001, and p<0.001, respectively). In multivariate analysis, oxygen saturation ≤94% (OR 2.47, CI 1.57–3.86), ferritin levels <338 ng/mL (OR 2.63, CI 1.69–4.07), and PCT higher than 0.2 ng/mL (OR 1.74, CI 1.11–2.72) were independent risk factors for co-infection at hospital admission owing to COVID-19. Conclusions: Bacterial co-infection in patients hospitalized for COVID-19 is relatively common. However, clinicians could spare antibiotics in patients with PCT values <0.2, especially with high ferritin values and oxygen saturation >94%.